Taylor bubble formation and flowing in a straight millimetric channel with a cross-junction inlet geometry Part II: Gas-liquid mass transfer. (31st August 2022) - Mei, Mei; Le Men, Claude; Loubière, Karine; Hébrard, Gilles; Dietrich, Nicolas
Graphical abstract: Highlights: Mass transfer was studied during bubble formation at a cross-junction. Accuracy of resazurin-based technique was improved by advanced image systems. Different mechanisms were observed for the developing O2 concentration fields. Oxygen concentration fields were measured during and after bubble pinch-off. A scaling law relating k L a and f c was proposed to gather literature data. Abstract: Using the resazurin-based colorimetric technique and advanced image acquisition, the equivalent oxygen concentration fields inside the liquid slugs were measured during and after the bubble formation stage at a cross-junction in a straight millimetric channel. Firstly, two different mechanisms were identified for the development of oxygen concentration fields depending on the two-phase Reynolds numbers (ReTP ). Under low ReTP, a jet-like central oxygen concentration 'finger' occurred between the newly formed bubble and the gas finger at the bubble pinch-off point. Right after the bubble pinch-off, the dissolved oxygen was transported first by the entering liquid from two side inlets, and later by the developing recirculation loop inside the liquid slug. Under higher ReTP, two highly concentrated oxygen concentration spots were formed near the bubble rear and the channel wall region, and a much more complex flow structure in the liquid slug appeared. Then, whatever the operating conditions, it was observed that the averaged oxygen concentrations inside the liquid slug followed a nearly linear relation as a function of the axial position in the channel, and that the related mass flux density decreased as far as the bubbles flowed along the channel's length. The bubble formation process could be decomposed into three stages when considering the temporal evolution of the cumulated oxygen mass and depending on the development of the liquid slug. At last, the overall volumetric liquid side mass transfer coefficients ( k L a ) were deduced from the concentration fields, and found to linearly increase with the recirculation frequencies, leading to a scaling law.